Clinical Outcomes of Treatment of Mid-Shaft Clavicle Fractures Using Anatomical Plating - Khanal, Siddhartha; Wahegaonkar, Krishna Da.; Khanal, Sagun (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Clavicle fractures are among the most common fractures in traumatic injuries around the shoulder girdle. Different treatment options are tried for its management, which include conservative as well as operative. Open reduction and internal fixation have become the mainstay of treatment for most midshaft clavicle fractures as this method restores the normal anatomy and biomechanics of the clavicle. This prospective study evaluated the effectiveness of anatomical pre-contoured plates in clavicle fractures. METHODS This study was carried out on a total of 40 patients above 18 years. The functional outcome was evaluated postoperatively using the Constant and Murley scoring system, which is based on eight parameters, namely: pain, activity level, arm positioning, the strength of abduction, forward flexion, lateral elevation, external rotation, and internal rotation. RESULTS There were thirty-one males and nine females with a mean age of 34±14 years. Six patients had associated injuries. The mean duration of surgery was 66±15 minutes. All fractures united in anatomical position and complications were noted in eight patients. Three patients had hardware prominence, one developed a postoperative infection, one had local hypoesthesia, two had a hypertrophic scar, and one had a hardware failure. At the end of the study, 75% of patients had excellent results with an overall Constant shoulder score of 90.9. CONCLUSION This study shows that displaced midshaft clavicle treated with pre-contoured plate osteosynthesis gives an anatomical reduction, early return to pre-injury level activity, and excellent functional results in most patients.